H-GRASP: the feasibility of an upper limb home exercise program monitored by phone for individuals post stroke. Issue 9 (24th April 2017) - Simpson, Lisa A.; Eng, Janice J.; Chan, May
Abstract: Purpose : To investigate the feasibility of a phone-monitored home exercise program for the upper limb following stroke.Methods : A pre-post double baseline repeated measures design was used. Participants completed an 8-week home exercise program that included behavioural strategies to promote greater use of the affected upper limb. Participants were monitored weekly by therapists over the phone. The following feasibility outcomes were collected: Process (e.g. recruitment rate); Resources (e.g. exercise adherence rate); Management (e.g. therapist monitoring) and Scientific (e.g. safety, effect sizes). Clinical outcomes included: The Chedoke Arm and Hand Inventory, Motor Activity Log, grip strength and the Canadian Occupational Performance Measure.Results : Eight individuals with stroke were recruited and six participants completed the exercise program. All but one of the six participants met the exercise target of 60 minutes/day, 6 days/week. Participants were stable across the baseline period. The following post-treatment effect sizes were observed: CAHAI (0.944, p =  0.046); MALQ (0.789, p =  0.03) grip strength (0.947, p =  0.046); COPM (0.789, p =  0.03). Improvements were maintained at three and six month follow ups.Conclusions : Community dwelling individuals with stroke may benefit from a phone-monitored upper limb home exercise program that includes behavioural strategies that promote transfer of exercise gains into daily upper limb use. Implications for Rehabilitation: A repetitive, task-oriented home exercise program that utilizes telephone supervision may be an effective method for the treatment of the upper limb following stroke This program is best suited for individuals with mild to moderate level impairment and experience a sufficient level of challenge from the exercises An exercise program that includes behavioural strategies may promote transfer of exercise gains into greater use of the affected upper limb during daily activities